2006
DOI: 10.1089/aid.2006.22.232
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Parameters of Nevirapine and Efavirenz in Relation to Antiretroviral Efficacy

Abstract: Optimal adherence is essential for successful antiretroviral therapy. We analyzed the relation between minimum plasma drug concentration (Cmin) and total drug exposure over 24 hr (AUC24) with virologic failure for therapy-adherent patients in the nevirapine (NVP) and efavirenz (EFV) groups of the double nonnucleoside study (2NN), which compared the efficacy of NVP and/or EFV together with stavudine and lamivudine. The objective was to find cutoff values of the Cmin and AUC24 below which the risk of virologic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 32 publications
2
47
1
Order By: Relevance
“…These data are not easy to interpret because they include data from the two other studies mentioned [11,12], but the summary implication of the results is that the minimal effective concentration of EFV is likely to vary depending on the activity of the other drugs used in the combination. In the PK/PD substudy of 2NN, comprising only previously treatment-naïve patients, a C trough < 1,100 ng/ml was associated with an increased risk of virological failure, although the positive predictive value for virological failure was very low [14]. In this study, 1,100 ng/ml was the imputed median C trough of the population; thus, the EFV exposure in that study seems to be lower than in other study populations (see [7,15,16]).…”
Section: Discussionmentioning
confidence: 97%
“…These data are not easy to interpret because they include data from the two other studies mentioned [11,12], but the summary implication of the results is that the minimal effective concentration of EFV is likely to vary depending on the activity of the other drugs used in the combination. In the PK/PD substudy of 2NN, comprising only previously treatment-naïve patients, a C trough < 1,100 ng/ml was associated with an increased risk of virological failure, although the positive predictive value for virological failure was very low [14]. In this study, 1,100 ng/ml was the imputed median C trough of the population; thus, the EFV exposure in that study seems to be lower than in other study populations (see [7,15,16]).…”
Section: Discussionmentioning
confidence: 97%
“…Minimum plasma concentrations define therapeutic success, while maximum concentrations define the threshold for adverse drug reactions [17,18]. High intrapatient variability in efavirenz plasma trough concentration, as measured using the integrated pharmacokinetic adherence measure (IPAM) score, was associated with higher risk of viral rebound [2], while Pfister et al demonstrated that a 100% increase in clearance above the population mean was associated with clinical failure among highly active antiretroviral therapy (HAART)-naïve patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma samples for drug concentrations of both ZDV/3TC and efavirenz were obtained 14 (IQR 13-15) hours and 13 (IQR [13][14] hours after the previous doses at 2 and 4 weeks, respectively. Mean plasma antiretroviral drug concentrations did not differ between patients with diarrhea and controls at Week 2 or Week 4; nor did the geometric mean values for each antiretroviral drug differ, Table 2 .…”
Section: Resultsmentioning
confidence: 99%